DENSITY OF PLANT TYPES AND MAINTENANCE IN MAJU JAYA HKM AGROFORESTRY SYSTEM, HUJUNG VILLAGE, WEST LAMPUNG - Surnayanti Surnayanti; Machya Kartika Tsani; Trio Santoso; Rahmat Safe’i; Abdul Jalal (JURNAL HUTAN PULAU-PULAU KECIL, 2022)
Community forest is a state forest that is utilized for the empowerment of local communities (Permenhut P.88/Menhut-11/2014). Agroforestri is one way to manage forest plants with a combination of agricultural crops with the hope of improving the community's economy without having to destroy the forest by knowing the density of plant species and maintaining plants. Knowing the density of species and plant maintenance is very important because to know the type of plant vegetation it is necessary to do the type of density while to know the productivity of plants it is necessary to know plant maintenance techniques. This study aims to determine the diversity of plant species in HKm Maju Jaya Pekon, Belalau District, West Lampung. This research was conducted in March 2021. Based on the results of the research, the density of each plant population was found, with the highest density being the coffee plant (Coffea robusta) of 929.83 individuals/ha. For the tree phase, the highest density was occupied by Jackfruit (Artocarpus heterophyllus) by 22.9 individuals/ha. The highest percentage is weed control and branch pruning, which is as much as 100% of all respondents carrying out fertilization activities as much as 56.7%. Embroidery activities were 36.7%, pendangiran activities were 23.3%, pest and disease control activities were 6.7% and thinning activities were 6.7%.